Cognitive Action Theory: An Overview - Baer, Wolfgang (Newest Updates in Physical Science Research Vol. 12, 2021)
Incorporating a conscious 1st person observer in scientific theories has been hampered by the lack of physically viable mind/body models. I will present a Cognitive Action Theory (Baer 2020) model of an integrated mind/body system and identify the process of creating conscious experience as the basic building block of reality. This building block is a cyclic process in time, connecting the first person experience with its 3d person physical models so that conscious phenomena are possible. To allow the construction of such a basic building block we propose a fundamental shift to consider what we do to be conscious as an a-priory activity that must be happening for us to be able to ask the question, “How can conscious beings exist in our physical world?” This shift means first asking, “How does the memory of a physical world exist in a conscious being”? The answer to this question leads to Conscious Action Theory (CAT) and the physical formulation of a conscious being as a self contained action cycle with the mental and physical phases. This activity contains both qualia and its explanation to produce what physicist Archibald Wheeler [1,2] described as a self measuring explanatory cycle. At this level of abstraction such a cycle of activity can accommodate any belief system defining physical reality as an explanation for personal experience and therefore provide a framework which accommodates both scientific and spiritual traditions. Visualizing such an abstract activity as the motion of masses and charges allows us to couple what we do to the formalism of classic and quantum physics. Such a theory integrates the subjective and objective aspect of our experience in a single physical framework, reducing to the linear quantum formalism when the motions involved are small enough to be reversible [3,4].